Unchanged pediatric out-of-hospital cardiac arrest incidence and survival rates with regional variation in North America. (October 2016) - Fink, Ericka L.; Prince, David K.; Kaltman, Jonathan R.; Atkins, Dianne L.; Austin, Michael; Warden, Craig; Hutchison, Jamie; Daya, Mohamud; Goldberg, Scott; Herren, Heather; Tijssen, Janice A.; Christenson, James; et al.
Abstract: Aim: Outcomes for pediatric out-of-hospital cardiac arrest (OHCA) are poor. Our objective was to determine temporal trends in incidence and mortality for pediatric OHCA. Methods: Adjusted incidence and hospital mortality rates of pediatric non-traumatic OHCA patients from 2007–2012 were analyzed using the 9 region Resuscitation Outcomes Consortium—Epidemiological Registry (ROC-Epistry) database. Children were divided into 4 age groups: perinatal (<3 days), infants (3 days–1 year), children (1–11 years), and adolescents (12–19 years). ROC regions were analyzed post-hoc. Results: We studied 1738 children with OHCA. The age- and sex-adjusted incidence rate of OHCA was 8.3 per 100, 000 person-years (75.3 for infants vs. 3.7 for children and 6.3 for adolescents, per 100, 000 person-years, p  < 0.001). Incidence rates differed by year ( p  < 0.001) without overall linear trend. Annual survival rates ranged from 6.7–10.2%. Survival was highest in the perinatal (25%) and adolescent (17.3%) groups. Stratified by age group, survival rates over time were unchanged (all p  > 0.05) but there was a non-significant linear trend (1.3% increase) in infants. In the multivariable logistic regression analysis, infants, unwitnessed event, initial rhythm of asystole, and region were associated with worse survival, all p  < 0.001. Survival by region ranged from 2.6–14.7%. Regions with the highest survival had more cases of EMS-witnessed OHCA, bystander CPR, and increased EMS-defibrillation (all p  < 0.05). Conclusions: Overall incidence and survival of children with OHCA in ROC regions did not significantly change over a recent 5 year period. Regional variation represents an opportunity for further study to improve outcomes.